ANALISIS PERBEDAAN PRODUKTIVITAS KERJA KARYAWAN SERIKAT PEKERJA DAN NON-SERIKAT PEKERJA PADA SEKTOR RITEL DI JAKARTA - Eny Ariyanto; Syamsul Ghofur (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: The purposes of this study were to examine the differences in the productivity of employees who join and not to join a union, and to study the effect of union instrumentality on the productivity of employees who joined the union in the retail sector in Jakarta. This study used survey method, the design of the study using descriptive, comparative and causality analysis. Using convenience sampling as a method of data collection, the study used as many as 243 data respondents. The resultsof a comparative analysis using Independent Sample T-Test concluded that the productivity of employees who join and not to join a union was not significantly different. The results of causality analysis using simple regression analysis concluded that there was a positive and significant impact of union instrumentality on the productivity of employees in the retail sector. Correlation between union instrumentality with productivity showed a very weak correlation. Union instrumentality variable affecting productivity variable very low.Keywords: productivity, retail, unions, comparative, instrumentality, affecting